UJI KANDUNGAN SENYAWA BORAKS PADA MIE AYAM DI WILAYAH BANDAR KOTA KEDIRI - Wiwik Werdiningsih (Cross-border, 2023)
Sodium borate |functions as a preservative but is dangerous like boric acid so it is prohibited from being used in food products. This study was conducted to determine the borax content in chicken noodles sold in Kediri City. The samples used in this study were taken from 5 chicken noodle traders in the Bandar Kota Kediri area. The methods used include flame test and tumeric paper test. For the flame test after the noodle sample is incandescent, if the result is a blue flame, it means that it does not contain borax. If the flame test is green, it shows a positive result containing borax. For tumeric paper test, if it gives a yellow color, it shows negative, it does not contain borax. The tumeric test shows a positive result if the tumeric paper gives it a brick-red color. The results of this study showed that wet noodles circulating in the Bandar Kota Kediri area did not contain borax.